Health-care providers’ preparedness for H1N1/09 influenza prevention and treatment in Dar es Salaam, Tanzania - Kamuhabwa, Appolinary; Chavda, Reena (The Journal of Infection in Developing Countries, 2011)
Introduction: In Tanzania, the first case of H1N1/09 influenza was reported in September 2009. By March 2010, the reported number of cases was 770 with one death. Due to shortage of qualified human resources, essential medicines and laboratory supplies in health facilities, it was not known how well health-care providers in the country were prepared to deal with the pandemic. Methodology: The study was conducted from December 2009 to May 2010 in public hospitals and private community pharmacies in Dar es Salaam, Tanzania. Fifty-three prescribers and 200 dispensers were interviewed to assess their knowledge on the prevention and treatment of H1N1/09 influenza, and dissemination of correct information to the public regarding the pandemic. Results: Most participants had inadequate knowledge on the transmission, prevention and management of H1N1/09 influenza. The majority of prescribers knew neither the antiviral drugs recommended for the treatment of H1N1 influenza (64%) nor their adverse effects (92.5%). The drug dispensers' knowledge was also inadequate regarding the transmission, prevention and treatment of H1N1/09 influenza. Forty-one (20.5%) salespersons without formal training in pharmaceutical or medical sciences were found dispensing and supervising the pharmacies. Most participants had misconceptions on how H1N1/09 virus was transmitted. Conclusion: The results of the study revealed gaps in the knowledge of the health-care providers on the prevention and treatment of H1N1/09 influenza infection. This indicates the need for strengthening of health-care systems and provision of continuing education and professional development for health-care providers on new and re-emerging diseases in the community.